A Case of Nivolumab-Induced Severe Mononeuropathy Multiplex and Rhabdomyolysis. (22nd October 2017) - Sakai, Katsuya; Mochizuki, Hitoshi; Mochida, Kosuke; Shiomi, Kazutaka; Amano, Masahiro; Nakazato, Masamitsu
Abstract : We report an 81-year-old man with multiple liver metastases after tumorectomy for primary mediastinal malignant melanoma, who experienced limb weakness and sensory disturbance after nivolumab monotherapy. He was diagnosed with nivolumab-induced mononeuropathy multiplex and rhabdomyolysis based on serologic examination, muscle biopsy, magnetic resonance imaging of the limbs, and a nerve conduction study. A course of intravenous methylprednisolone (mPSL) was initiated at 1 g/day for 3 days. After that, oral prednisolone (PSL) was started at 1 mg/kg/day and gradually tapered. Limb muscle strength improved, but when PSL was reduced to 0.3 mg/kg/day, the weakness recurred, and a nerve conduction study showed exacerbation of mononeuropathy multiplex. The patient was again administered intravenous mPSL (0.5 g/day for 3 days) followed by oral PSL at 0.5 mg/kg/day, and his neurological symptoms improved. Nivolumab, an immune checkpoint inhibitor, is used for the treatment of advanced melanoma and other cancers and causes various immune-related adverse events (irAEs). However, neurological irAEs related to nivolumab are rare. Furthermore, there are no reports of simultaneous nerve and muscle impairment. Unexpected irAEs affecting various organs should be recognized and treated appropriately.